Sleep and chronobiology in cluster headache. (October 2015) - Barloese, M; Lund, N; Petersen, A; Rasmussen, M; Jennum, P; Jensen, R
Background and aim: M.R. present address: PAIN, National Institutes of Health, Bethesda, MD, USA Cluster headache (CH) is the headache disorder with the strongest chronobiological traits. The severe attacks of pain occur with diurnal and annual rhythmicity but the precise rhythm and involvement of potential zeitgebers is unknown. Patients complain of poor sleep quality yet this has never been studied. We investigated triggers, rhythms, sleep quality and chronotypes in CH. Methods: Patients and controls completed questionnaires and structured interviews composed of new and previously validated parts including the Pittsburgh Sleep Quality Index (PSQI) and Morningness-Eveningness Questionnaire (MEQ). Patients were characterized by a CH index, a unified measure of headache burden. Results: A total of 275 CH patients and 145 matched controls were included. The most common trigger was sleep (80%) and a relationship between clusters and daylight was identified. Of the patients, 82.2% reported diurnal and 56% annual rhythmicity. Patients reported impaired sleep quality (PSQI) ( p  < 0.0001) and an inverse relationship between time passed since last attack and sleep quality was identified ( p  < 0.0001). The CH index was positively related to the PSQI ( p  < 0.0001). Conclusion: Diurnally, CH exhibits a relationship with night-time and annually with daylight hours. Patients' sleep quality is reduced compared with controls. Results suggest a complex relationship as sleep quality improves between clusters, but remains pathological.